Social Construction of Islamic Local Tradition in Malay Community, Indonesia - Jubba, Hasse; Suprianto, Bibi; Prasojo, Zaenuddin Hudi; Darmadi, Didi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Religion in the Malay community is not only seen as something related to belief but also concerns issues of identity and symbols in other community groups. This study intends to look at the social construction of Islamic local tradition in the Malay community. This study argues that it turns out that the social construction of religion builds a cultural concept in Islamic religious values as an identity through the customs of the Malay community. In response to that argument, the question arises: How is the form of social construction of religion in the Malay community? And how does the social construction of religion affect the social life of religion in the Malay community? This research uses a media approach and literature review that explains the social construction of Islamic traditions in Malay society. The results of this study indicate that the social construction of religion in the Malay community has several important conditions. (1) religion-based tradition orientation, (2) close solidarity in religious social construction, (3) the existence of religion-based legal norms in the Malay community, and (4) a proud identity that is superior to the Malay community. These findings conclude that religious social construction in Malay society shows that religious and tribal identities develop as a religious social construction.Agama dalam masyarakat Melayu tidak hanya dilihat sebagai sesuatu yang berkaitan dengan kepercayaan, tetapi juga menyangkut persoalan identitas dan simbol pada kelompok masyarakat lainnya. Penelitian ini bermaksud untuk melihat konstruksi sosial dari tradisi lokal Islam pada masyarakat Melayu. Penelitian ini berargumen bahwa ternyata konstruksi sosial agama membangun konsep budaya dalam nilai-nilai agama Islam sebagai identitas melalui adat istiadat masyarakat Melayu. Dengan itu, penelitian ini merumuskan sebuah pertanyaan bagaimana bentuk konstruksi sosial agama pada masyarakat Melayu? Dan bagaimana pengaruh konstruksi sosial agama terhadap kehidupan sosial keagamaan pada masyarakat Melayu? Penelitian ini menggunakan media dan studi literatur yang menjelaskan tentang kehidupan sosial dan agama dalam masyarakat Melayu. Hasil penelitian ini menunjukkan bahwa konstruksi sosial agama pada masyarakat Melayu menunjukkan bahwa; (1) adanya orientasi tradisi berbasis agama; (2) adanya solidaritas dalam konstruksi sosial agama; (3) adanya norma hukum berbasis agama pada masyarakat Melayu; dan (4) adanya kebanggaan akan identitas yang lebih unggul pada masyarakat Melayu. Dengan hasil ini, disimpulkan bahwa konstruksi sosial keagamaan dalam masyarakat Melayu menunjukkan bahwa identitas agama dan kesukuan berkembang sebagai konstruksi sosial keagamaan.